Building fortress Europe : the Polish-Ukrainian frontier - Follis, Karolina S. (Karolina Szmagalska-) (Democracy, citizenship, and constitutionalism., 2012)
Building Fortress Europe is an ethnographic examination of the human, social, and political consequences of developing a specialized, targeted, and legally advanced border regime in the enlarged European Union, exploring the intersection between border policing and the lives of migrants, framed by the contradictions of European integration.